Experimental Evaluation of Anthelmintic effect of Gallic Acid - Patel, Mohit; Ganeshpurkar, Aditya; Bansal, Divya; Dubey, Nazneen (Pharmacognosy Communications)
Background: Helminth infestation is most prevalent infestations by parasites, which affects large part of world’s population. It is one of the leading causes of malnutrition among children. Gallic acid (3,4,5 trihydroxybenzoic acid), a plant polyphenol, is a naturally abundant gallotannin, which is found in vegetables, fruits, legumes and beverages. The present study was undertaken to explore anthelmintic activity of gallic acid. Materials and Methods: Five concentrations (25, 50 and 100 mg/ml) of gallic acid were studied in the anthelmintic bioassay to determine the paralysis time and death time in the worm Pheretima posthuma. Piperazine citrate was used as standard in the study. The results are expressed as mean ± standard error of mean. Experiments were always performed in triplicates. Results: Gallic acid exposure to worms caused a dose dependent paralysis and death. At lower concentration, (10 mg/ml) paralysis time was 29.27 ± 1.62 min and time for death was 52.11 ± 1.92 min. Increase in concentration of gallic acid (100 mg/ml) caused paralysis within 20 min (20.97 ± 1.93) and death was observed within first 30 min (30.11 ± 1.63) Conclusion: The study confirms the significant anthelmintic activities of gallic acid. However further studies on tape worms and other worms is needed to be undertaken.
Keywords: Anthelmintic; Gallic acid; Piperazine citrate